Combating (Child) Human Trafficking: Building Capacity - John Winterdyk (Oñati Socio-Legal Series)
The presentation/paper focuses on the challenges and necessity of building capacity at local, national, and international levels with a focus of how to more effectively combat trafficking in human beings (THB). Insight from several of initiatives are shared with the aim of illustrating how to capitalize on the vast number of opportunities that already exist at these levels and how they might be coordinated to enable collaborative work in an informed and dynamic manner to combat human trafficking. Information from several recent research projects that focus on some of these same issues is also incorporated into this paper.